Childhood maltreatment and prosocial behavior among Chinese adolescents: Roles of empathy and gratitude. (March 2020) - Yu, Guoliang; Li, Sen; Zhao, Fengqing
Abstract: Background: Childhood maltreatment, including both abuse (physical, emotional, and sexual) and neglect (physical and emotional), is especially detrimental to adolescent development. However, most studies have been conducted within a psychopathological framework and focused on its role in exacerbating negative outcomes. Its adverse effect on adolescents' positive functioning, including empathy, gratitude, and prosocial behavior, is relatively underexplored. Objective: Guided by attachment theory, empathy-altruism hypothesis, and broaden-and-build theory of positive emotions, this study examined the relationship between childhood maltreatment and prosocial behavior using a multiple mediation model that included empathy and gratitude as hypothesized mediators. Methods: A sample of 897 adolescent students (45.80 % males and 54.20 % females; Mage = 15.41 years, SD = 1.73) completed questionnaires regarding demographics, childhood maltreatment, empathy, gratitude, and prosocial behavior. Results: The results indicated that the prevalence rates of physical abuse, physical neglect, emotional abuse, emotional neglect, and sexual abuse were 10.81 %, 58.97 %, 19.84 %, 53.51 %, and 15.61 %, respectively. After controlling for demographic covariates, the results revealed that: (a) childhood maltreatment was negatively associated with prosocial behavior; (b) empathy and gratitude mediated the link between childhood maltreatment and prosocial behavior in a parallel fashion; and (c) empathy and gratitude also mediated the link between childhood maltreatment and prosocial behavior in a sequential fashion. Conclusions: Childhood maltreatment is negatively related to adolescent prosocial behavior, and the relation is mediated by empathy and gratitude both parallelly and sequentially.